A simple method for the measurement of metabolic heat production rates during solid‐state fermentations using β‐carotene production with Blakeslea trispora as a model system. Issue 6 (10th February 2017) - Altwasser, Vivien; Pätz, Reinhard R.; Lemke, Thomas; Paufler, Sven; Maskow, Thomas
Abstract : Solid‐state fermentation (SSF) technology has been rapidly developed for the past 10 years as a production platform for secondary metabolites, biofuels, food, and pharmaceuticals. Yet, the main drawback of SSF is the local temperature rise of up to 20 K, which potentially reduces the strain activity and inactivates heat sensible products. Due to the low heat capacity and thermal conductivity of mixtures of air with plant material, in comparison to aqueous suspensions in submerged fermentations, heat from metabolic processes is less efficiently dissipated. The exact knowledge of the metabolic heat generation during SSF processes is crucial to guide strategies against overheating. In this work, a simple method using a cost‐efficient multichannel instrument is proposed, which allows the determination of heat generation during SSF processes. This method was successfully tested and validated with Blakeslea trispora producing β‐carotene during growth on barley. Additionally, the consequences of the generated metabolic heat during SSF on temperature rise and water evaporation were discussed. Finally, changes in growth and product concentration could also be detected by the heat signal, implying the potential as a timesaving screening method.